Silicon DiOxide is The Most Abundant Mineral in the Earth’s Crust: How Toxic is It? - Prakash, Ankita (East Carolina University, 2023)
Silicon DiOxide, commonly known as silica, is the most abundant mineral in the earth’s crust, and ubiquitous in commercial use. Although harmless in its native state, its nanoparticle counterpart can be highly toxic. Nanoparticles are materials <100 nm in at least one dimension and highly sought after for commercial purposes. The biomedical, pharmaceutical, cosmetic, and energy industries are just a few amongst many others that conventionally utilize nanoparticles in some form (Biswas and Wu, 2005). Despite their prevalence, little is known about their possible toxic effects on biotic factors. Due to their recent emergence, their bioavailability remains largely unknown. Bacterial and living cells have proven to be able to uptake nanoparticles from their environment, which initiates a bioaccumulation ladder (Biswas and Wu, 2005). This study aims to understand the effects of increasing environmental abundance of SiO2 on Camelina sativa plant growth morphology and cellular oxidative stress. It is hypothesized that SiO2 significantly hinders C. sativa growth by increasing the accumulation of Reactive Oxygen Species (ROS) in cells. Five experimental groups were prepared with increasing SiO2 concentrations of 0%, 0.01%, 0.05%, 0.1%, and 0.5%. The seeds were sterilized and allowed to germinate for 14 days. Statistical data analysis proved a higher abundance of silica to significantly decrease quantity, weight, and length of shoots and roots. Significant increase in hydrogen peroxide accumulation and peroxide dismutase activity, and significant decreases in root vigor activity indicated increased production of ROS.
Keywords: Nanoparticles, Silicon DiOxide, ROS, Oxidative Stress, Plant growth and Development